Juridical Analysis of Brand Dispute Resolution in Indonesia - Dipo Selogiri, Siana (Jurnal Legisci, 2023)
A good product must have good quality in itself and requires a brand so that consumers can easily remember it. Brands attached to a product, goods, and services are likened to two sides of a coin: closely related and needy. A critical point in trademark protection is that a mark cannot be registered based on an application filed by an applicant in bad faith. A registered mark is valid and has been registered at the Director General of IPR and obtained a registration number. One of the exciting cases regarding the brand dispute was between Irawan Widjaja and Lancaster, which was resolved through mediation. Mediation is a negotiation involving a third party who has expertise regarding effective mediation procedures and can help in conflict situations to coordinate their activities to be more effective in the bargaining process. This type of research is juridical normative, an approach based on the primary legal material by examining theories, concepts, legal principles, and laws and regulations related to this research. The result of this study is that the legal step chosen by Irawan Widjaja, namely through mediation, is very wise and appropriate, considering that the goal is to resolve it as quickly as possible at a relatively minor cost.